Penguatan Literasi Numerasi Sekolah Dasar pada Guru SDN Belitung Selatan 1 - Djamilah, Soraya; Istiqamah; Leha, Noor (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Language and numeracy skills are the initial pillars of learning, so that children can gain meaningful knowledge and encourage critical thinking and responsiveness to the environment. Strengthening numeracy literacy as an ability or skill in reading and calculating both textually and contextually. This community service activity aims to 1) instill the fundamental concepts of basic numeracy literacy needed by elementary school students, 2) present a variety of activities or programs that can be implemented in schools that are integrated into subjects, or indirectly through programs outside of learning hours, and 3 ) describes the application of AKM standards for measuring the achievement of numeracy literacy levels in elementary school children. This Community Service is carried out using a focused discussion method, and outreach to teachers at SDN Belitung Selatan 1 Banjarmasin